Signifikansi Penerapan Literasi Ekonomi Islam di Perguruan Tinggi: Kajian Teoritis - Ahmad Lukman Nugraha; Arie Rachmat Sunjoto; Adib Susilo (Islamic Economics Journal, 2019)
Literacy at higher education institutions in Indonesia is at a low level where BPS 2018 data states that of the total Indonesian population aged 15 years and over who participated in higher education at 18.59% of the pure enrollment rate at the level of education in Indonesia. That means that Indonesians who continue their education to a higher level are lower than those who go straight to work after graduating from high school. The low level of literacy in general, is in line with the low economic literacy and Islamic economics, especially at Islamic higher education institutions. This is proven by the low knowledge of students about financial literacy that has an impact on individual financial management. Based on the background of the problem, the significance of Islamic economic literacy at universities in Indonesia needs to be studied and researched both theoretically and practically. Therefore, the purpose of this study is to describe the significance of literacy in higher education institutions in Indonesia. The method used in this research is descriptive qualitative with a literature approach used to study theories related to literacy so that it can emerge as to the significance of Islamic economic literacy in universities. The results of this study found that economic literacy is absolute necessity so students can compete globally and even become world-class inventors. But economic literacy alone is not enough, there needs to be values that keep economic activity on track in accordance with religious norms. Therefore, the literacy of Islamic economics in all aspects is an urgency that needs to be considered by individuals and educational institutions to be able to encourage people to help each other in economic independence with students as literacy agents.